2003
DOI: 10.1074/jbc.m304182200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C β Is Required for Human Monocyte Chemotaxis to MCP-1

Abstract: Monocyte chemoattractant protein 1 (MCP-1) is important in attracting monocytes to sites of inflammation. Using predominantly pharmacological approaches, prior studies have indicated that serine/ threonine kinases are involved in the MCP-1-induced signaling pathways. We report here that there is substantial inhibition of MCP-1-stimulated chemotaxis of human monocytes treated with inhibitors selective for the subset of serine/threonine kinases, protein kinase C (PKC). Selective inhibitors of PKC such as GF10920… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 65 publications
3
46
0
Order By: Relevance
“…Interestingly, a significant reduction was also observed in the basal migration of GFP-PKCβ-DN expressing monocytes in the absence of MCP-1. These data support our previous observations, using pharmacologic inhibitors and antisense oligonucleotides, that identified an important regulatory role of PKCβ in monocyte chemotaxis to MCP-1 in vitro (Carnevale and Cathcart, 2003). They also highlight the success of our transfection procedure and feasibility of using GFP-expressing monocytes for in vivo studies.…”
Section: Gfp-pkcβ-dn Expressing Monocytes Display Reduced Chemotaxis supporting
confidence: 78%
See 4 more Smart Citations
“…Interestingly, a significant reduction was also observed in the basal migration of GFP-PKCβ-DN expressing monocytes in the absence of MCP-1. These data support our previous observations, using pharmacologic inhibitors and antisense oligonucleotides, that identified an important regulatory role of PKCβ in monocyte chemotaxis to MCP-1 in vitro (Carnevale and Cathcart, 2003). They also highlight the success of our transfection procedure and feasibility of using GFP-expressing monocytes for in vivo studies.…”
Section: Gfp-pkcβ-dn Expressing Monocytes Display Reduced Chemotaxis supporting
confidence: 78%
“…Previous studies from our lab identified PKCβ as a critical regulatorof human monocyte chemotaxis to MCP-1 in vitro using pharmacologic inhibitors and specific antisense oligonucleotides (Carnevale and Cathcart, 2003). To functionally validate our method of transfection, we investigated the role of PKCβ in monocyte migration by overexpressing GFP-PKCβ-WT as well as the dominant negative mutant, GFP-PKCβ-DN plasmid DNA.…”
Section: Expression Of Gfp-pkcβ-wt and The Gfp-pkcβ-dn Mutant In Monomentioning
confidence: 99%
See 3 more Smart Citations